Antibiotic residues of drinking-water and its human exposure risk assessment in rural Eastern China. (1st June 2023) - Wang, Yingying; Dong, Xiaolian; Zang, Jinxin; Zhao, Xinping; Jiang, Feng; Jiang, Lufang; Xiong, Chenglong; Wang, Na; Fu, Chaowei
Highlights: Antibiotics have been found in tap water and well water in rural Eastern China. The dominant contaminations in drinking-water samples were macrolides and sulfonamides. Drinking-water may be an important exposure source to antibiotics, inducing potential health risks. Ingestion route, compared with dermal contact, may be the primary mode of exposure to antibiotic residues in drinking-water. Abstract: Trace levels of antibiotics were frequently found in drinking-water, leading a growing concern that drinking-water is an important exposure source to antibiotics in humans. In this study, we investigated antibiotics in tap water and well water in two rural residential areas in Eastern China to assess the related human health exposure risks in drinking-water. Twenty-seven antibiotics were analyzed using ultra performance liquid chromatography coupled with triple quadrupole tandem mass spectrometry (UPLC-MS/MS). The average daily dose (ADD) and the health risk quotient (HRQ) for exposure to antibiotics in humans were evaluated using 10000 times of Monte Carlo simulations. Ten antibiotics were detected in drinking-water samples, with the maximum concentrations of antibiotic mixture of 8.29 ng/L in tap water and 2.95 ng/L in well water, respectively. Macrolides and sulfonamides were the predominant contaminants and showed the seasonality. Azithromycin had the highest detection frequencies (79.71-100%), followed by roxithromycin (25.71-100%) and erythromycin (21.43-86.96%). The estimated ADD and HRQ for human exposure to antibiotic mixture through drinking-water was less than 0.01 μg/kg/day and 0.01, respectively, which varied over sites, water types, seasons and sex. Ingestion route was more important than dermal contact route (10 −6 to 10 −4 μg/kg/day magnitude vs. 10 −11 to 10 −8 μg/kg/day magnitude). Macrolides also contributed mainly to health exposure risks to antibiotics through drinking-water, whose HRQ accounted for 46% to 67% of the total HRQs. Although the individual antibiotic and their combined effects contributed to acceptable health risks for human, the long-term exposure patterns to low-dose antibiotics in drinking-water should not be ignored.